Enrichment and characterization of extracellular vesicles from ex vivo one‐sided human placenta perfusion. (28th November 2020) - Zabel, Rachel R.; Bär, Christin; Ji, Jinlu; Schultz, Rowena; Hammer, Martin; Groten, Tanja; Schleussner, Ekkehard; Morales‐Prieto, Diana M.; Markert, Udo R.; Favaro, Rodolfo R.
Abstract: Problem: Extracellular vesicles (EVs) released by the placenta are packed with biological information and play a major role in fetomaternal communication. Here, we describe a comprehensive set‐up for the enrichment and characterization of EVs from human placenta perfusion and their application in further assays. Method of study: Human term placentas were used for 3 h ex vivo one‐sided perfusions to simulate the intervillous circulation. Thereafter, populations of small (sEVs) and large EV (lEVs) were enriched from placental perfusate via serial ultracentrifugation. Following, EV populations were characterized regarding their size, protein concentration, RNA levels, expression of surface markers as well as their uptake and miRNA transfer to recipient cells. Results: The sEV and lEV fractions from an entire perfusate yielded, respectively, 294 ± 32 µg and 525 ± 96 µg of protein equivalents and 2.6 ± 0.5 µg and 3.6 ± 0.9 µg of RNA. The sEV fraction had a mean diameter of 117 ± 47 nm, and the lEV fraction presented 236 ± 54 nm. CD63 was strongly detected by dot blot in sEVs, whereas only traces of this marker were found in lEVs. Both EV fractions were positive for the trophoblast marker PLAP (placental alkaline phosphatase) and annexin A1. EV internalization in immune cells was visualized by confocal microscopy, and the transfer of placental miRNAs was detected by quantitative real‐time PCR (qPCR). Conclusions: Enriched EV populations showed characteristic features of sEVs and lEVs. EV uptake and transfer of miRNAs to recipient cells demonstrated their functional integrity. Therefore, we advocate the ex vivo one‐sided placenta perfusion as a robust approach for the collection of placental EVs.